Efficacy according to blind independent central review: Post-hoc analyses from the phase III, randomized, multicenter, IPASS study of first-line gefitinib versus carboplatin/paclitaxel in Asian patients with EGFR mutation-positive advanced NSCLC - Yi Long Wu (2018)
© 2016 The Authors Objective The Phase III, randomized, open-label IPASS study (NCT00322452) of first-line epidermal growth factor receptor tyrosine kinase inhibitor (EGFR TKI) gefitinib versus carboplatin/paclitaxel for Asian patients with advanced non-small-cell lung cancer (NSCLC) showed that investigator-assessed progression-free survival (PFS) and objective response rate (ORR) were significantly prolonged in patients with EGFR mutation-positive NSCLC who received gefitinib versus patients with EGFR mutation-negative NSCLC. We report post-hoc analyses of IPASS data by blind independent central review (BICR), performed at the request of the US FDA, in a subset of patients with EGFR mutation-positive NSCLC. Patients and methods Eligible patients (aged ≥18 years; histologically/cytologically confirmed Stage IIB/IV adenocarcinoma NSCLC; non- or former light-smokers; treatment-naïve) were randomly assigned 1:1 to gefitinib (250 mg/day) or carboplatin (dose calculated to produce an area under the curve of 5 or 6 mg/mL/minute)/paclitaxel (200 mg/m 2 ). Primary endpoint: PFS. BICR analyses included PFS, ORR, and duration of response (DoR). Results Scans from 186 IPASS patients (gefitinib n = 88, carboplatin/paclitaxel n = 98) with EGFR mutation-positive NSCLC were available for BICR. Consistent with investigator-assessed results, in patients with EGFR mutation-positive NSCLC: PFS (hazard ratio 0.54; 95% confidence interval [CI] 0.38, 0.79; p = 0.0012) and ORR (odds ratio 3.00; 95% CI 1.63, 5.54; p = 0.0004) were significantly longer with gefitinib versus carboplatin/paclitaxel. The median DoR by BICR was 9.6 months with gefitinib and 5.5 months with carboplatin/paclitaxel. Conclusion BICR analysis of IPASS data support the original, investigator-assessed results. EGFR mutation-positive status remains a significant predictor of response to first-line TKI therapy.